Time matters: genetic composition and evaluation of effective population size in temperate coastal fish species - Francisco, Sara M. (2020)
Extensive knowledge on the genetic characterization of marine organisms has been assembled, mainly concerning the spatial distribution and structuring of populations. Temporal monitoring assesses not only the stability in genetic composition but also its trajectory over time, providing critical information for the accurate forecast of changes in genetic diversity of marine populations, particularly important for both fisheries and endangered species management. We assessed fluctuations in genetic composition among different sampling periods in the western Portuguese shore in three fish species.